Contribution to the Development of Personal Computing: the Legendary Compucorp 450 - Cholakov, Nikola (Research Papers, 2005)
During the organization of the Laboratory for Demographic Research/Labour and Social Protection Department of the University of National and World Economy in 1977 it became quite clear that no serious scientific work on demographic data analysis could be feasible without suitable computer technology. Let alone to develop a multi-dimensional data base for the population of Bulgaria which should facilitate building reasonable hypotheses for the future and verifying different forecasting alternatives. The head of the Laboratory Prof. Nicola T. Naoumov managed somehow to convince party and government authorities of that time that with paper and pencil only it is impossible to derive the desired scientific research products on such sensitive problems like demographic ones and to expect serious scientific support for the government policy on population. The outcome of these efforts was the equipment of the Laboratory with a present-day computer like Compucorp model 450.In this study the features of such a forerunner of personal computers are examined and it is attempted to reveal what tendencies could be spotted in the development of information technologies during the seventies of the last century.